Many “little Führers”? The “weight” of personal decree in the General Government of Poland: Peer reviewed article (Italian Review of Legal History, 2021)
The system based on National Socialist political doctrine was born neither accompanied by a legal cultural basis of its own, nor with the premise of “relying on” the State in order to reorganize German social and economic life. In fact, it was the numerous National Socialist jurists who elaborated a sort of “structure of legal sources” which constituted a reserve of legal instruments to be used to reach a point of “fusion” between institutional structure and political doctrine.The distorting effects that the new “National Socialist Law” had in the management of territories, especially in those occupied during the war, manifested themselves with greater intensity on Polish territory or, more precisely, on that portion of territory renamed Generalgouvernement für die besetzten polnischen Gebiete, more simply the General Government of Poland; both in the high levels of the Zivilverwaltung and in the administration of the local districts (Kreise), the personalisms of the officials manifested themselves strongly, also thanks to the use of forms of personal decree with different effectiveness. The objective of the “codification” of the regime thus became the object of exploitation, both by the upper echelons of the party (including Hitler), and by those who worked in the administration of the GG, especially some local officials. They, in different forms and with different intensity, fulfilled their functions as petty dictators, using juridically different and territorially limited versions of the personal decree.Frank found himself in the position of having to justify to his Führer the leadership of the «Gau of the Vandals» and his being at the same time a man of law. Hitler expressed his contempt for the category of jurists whom he considered “traitors to the people”, calling them «mentally handicapped from birth or destined to become so with the passage of time» and declared in a speech to the Reichstag on April 26, 1942 that he would have no «peace until every German was convinced that being a jurist was a shameful disgrace». Curiously, the actual exercise of power by the dictator, based on his undisputed personal and political authority, was justified on the juridical level by the doctrinal interpretation of some singular normative instruments, the Führererlasse, the maximum expression of “compromise”, between justification of existing power and an attempt to codify its strength and contents in a peculiar Nazi “constitutional” structure.They were never formally part of the German legal order, but were de facto an element approved and amply justified by the National Socialist juridical doctrine, which influenced the life of the Reich and the territories it controlled, feeding and amplifying that system of double institutional levels. which had its most chaotic realization in the GG. The attitude of absolute sovereign on the part of the Kreishauptmänner was typical in the local districts; even from these childish behaviors and from the ostentation of a pomp which was often the result of robbery and looting, it was possible to recognize both the amateurism of a large slice of the administrative staff, and the almost unlimited possibilities caused by the use of personal instruments in the hands of district chiefs.The command practice was based on recommended and unpunished violence: the existence of some very rare “oases of normal administration” depended exclusively on the will of the individual local leaders and on the resonance that their actions could have at the top of the state nomenclature. The way the population was treated was aimed at leaving a mark on German occupation policy and showing the efficiency of the administrators, through construction work (Aufbauarbeit) of a testimony of the historische Mission in Ostgebiet.The objective of this paper is to relate the instrument of personal decree with the powers of which they were at the same time cause and consequence, and the behavior of the individual officials who operated in the various institutional levels taken into account, mentioning some cases of an atypical administrative entity like GG.
Keywords: Führererlasse; Zivilverwaltung; Kreise; Hans Frank; Kreishauptmann; Stadthauptmann